The effect of dietary patterns on the incidence of illness in early childhood in the Special Region of Yogyakarta : A cross-sectional study using logistic regression analysis - Oktaviana Maharani; Arantika Meidya Pratiwi; Jasmin Adinda Solikhah; Adinda Setyaningsih; Riska Miftakhul Rahmasari; Retha Nurhaida Rahmadanti (Alma Ata University Press, 2026)
Background: Diet plays a crucial role in maintaining health status and boosting immune system of young children against different illnesses. The context based on ongoing pediatric illness due to suboptimal feeding patterns. An inadequate diet can depress the child's resistance and his ability to fight off illness. Objectives: This research aimed to analyse the effect of diet on child morbidity in Yogyakarta Special Region. Methods: This research was a quantitative study with a cross-sectional approach. The study population was all children aged 0–7 years in the Special Region of Yogyakarta, with a sample of 366 children selected using multistage cluster random sampling. Data analysis was performed using logistic regression analysis to determine the extent of the influence of diet on the incidence of illness. Results: The results showed that the majority of children had sufficient dietary patterns (51.9%), followed by good dietary patterns (44.3%) and poor dietary patterns (3.6%), while illness incidence was found in 48.6% of respondents. Logistic regression analysis indicated that dietary patterns significantly affected illness incidence among early childhood children (p = 0.012). Children with poor dietary patterns had a 7.23 times higher risk of experiencing illness compared to children with good dietary patterns (OR = 7.23). The Nagelkerke R Square value of 0.039 indicated that dietary patterns contributed 3.9% to illness incidence, while the remaining proportion was influenced by other factors not examined in this study. Conclusions: The conclusion of this study is that dietary patterns have a significant effect on the incidence of illness in early childhood, although the contribution is relatively small; therefore, strengthening other supporting factors for comprehensive child health is necessary.